A concept for multi-winner tenders for medicinal products with balancing between efficient prices, long-term competition and sustainability of supply - Németh, Gergely; Mágó, Mánuel László; Kaló, Zoltán; Lám, Judit; Balogh, Tamás; Brodszky, Valentin (Frontiers in Medicine, 2023)
Achieving price efficiency via tenders, the sustainability of competition, and the prevention of shortages are hot topics in the debates about shaping the pharmaceutical markets. Single-winner tenders receive growing criticism for concentrating on achieving low prices at the expense of the long-term maintenance of a competitive pharmaceutical industry, the security of continuous supply, and disregarding the therapeutic needs of patient populations with specific conditions. This paper aims at drafting a concept to assist the design of multi-winner tenders for medicinal products with a focus on supply and sales guarantees, price efficiency, and equity in access. The concept shall be generally applicable to all kinds of medicinal products including generics, biosimilars, and on-patent products in the out- and in-patient sector. Principles for multi-winner tenders for medicinal products are set and a number of delimitations are made in order to get rid of factors that prevent clairvoyance amid the various pricing and reimbursement systems when designing a concept. The steps to plan and implement a multi-winner tendering procedure are drafted on the basis of the defined principles. The tender should consist of planning, bidding, preparation, sales, and evaluation phases. Pharmaceutical companies shall make bids with price and quantity pairs, which shall be ranked by prices and if applicable then taking into account other factors. The tenderer shall predefine market shares to the various places of the ranking. A double ceiling shall be applicable for the sales of the winners: their sales must not exceed their quantity offer and the predefined market share applicable to their place in the ranking. The implementation of the concept will require the careful adjustment of the tender conditions to the specificities of the pharmaceutical market concerned on the one hand and to the local pricing and reimbursement system on the other hand.